REGIONAL PUBLIC SERVICE AGENCY (BLUD) FINANCIAL MANAGEMENT AT PUSKESMAS KARANGREJA, PURBALINGGA DISTRICT - Sugiyarti Sugiyarti; Ambari Ambari; Emiraldo Win Pazqara (Department of Public Administration, University Wijaykusuma Purwokerto, 2022)
This thesis is titled: